Recovery of rebaudioside A and stevioside from stevia reaudiana plant using solid liquid extraction - Muhammad Naufal Afif, Mohd Hanis (2018)
Solid-liquid extraction is a recovery process which the extracting solvent will recover component from solid. In this study, three extracting solvent been used which are absolute ethanol, acetone and distilled water. The solvent will extract two sweetening agents, rebaudioside A and stevioside from stevia rebaudiana plant. The sweetening agent was well known as natural sweetener with zero calorie and does not give adverse effect on human health. The objective of this study was to determine the best parameters to extract the highest amount of stevioside and rebaudioside A. The extraction was done in 3 phase. First phase to determine the best ratio between stevia and extracting powder, second phase to determine the best extracting time and third phase was to determine the best temperature. Ethanol was the best extracting solvent compared to acetone and water. Extraction of stevioside and rebaudioside A using ethanol in the most preferable parameter (ratio 1:25, 1 hour and 45℃) produced 12.48% yield of stevioside and 0.57% yield of rebaudioside A.